Histomorphological investigation of intrahepatic connective tissue for surgical anatomy based on modern computer imaging analysis. (22nd July 2020) - Ikeda, Tetsuo; Okano, Shinji; Hashimoto, Naotaka; Kimura, Koichi; Kudo, Kensuke; Tsutsumi, Ryosuke; Sasaki, Shun; Kawasaki, Junji; Miyashita, Yu; Wada, Hiroya
Abstract: Background/Purpose: Computer‐assisted tissue imaging and analytical techniques were used to clarify the histomorphological structure of hepatic connective tissue as a practical guide for surgeons. Methods: Approximately 5000 histological slides were prepared from liver specimens of five autopsied patients. Three‐dimensional (3D) reconstruction was performed and subjected to computer imaging analysis. Scanning electron microscopy was also performed on the liver specimens. Results: The 3D reconstructed images revealed the running form of the vasculature and the relationship between the hepatic lobule and connective tissue. The hepatic capsule or portal pedicle was consistently located at the periphery of the hepatic lobules. An artificial intelligence random forest approach clearly segmented hepatic cells, type I collagen (CF), type III collagen (RF), and other cells. The hepatic lobule, portal region, and hepatic capsule were significantly distinguished based on CF and RF occupancy. The capsule directly covering the liver lobule with an RF concentration up to 87% was provisionally named the proper hepatic capsule. The existence of a proper hepatic ligament with distinct occupation rates of CF and RF was also suggested. Conclusions: The identified proper hepatic capsule and ligament can be important markers for demarcating the dissecting layer during surgical procedures. Abstract : Highlight Computer‐assisted tissue imaging and analytical techniques were used to clarify the histomorphological structure of hepatic connective tissue. Ikeda and colleagues focused on the capsule surrounding the hepatic lobule itself. The identified proper hepatic capsule and ligament appear to be an important structure for demarcating the dissecting layer during surgical procedures.